THEMATIC PROGRESSION OF STUDENTS’ NARRATIVE WRITING - ARSEN NAHUM PASARIBU; TIARA K PASARIBU; SARMA PANGGABEAN (JURNAL ILMIAH SIMANTEK, 2019)
This study is aimed to find the types of thematic progression of students’ narrative writing and the way of theme and rheme was developed. The analysis is based on textual function of Systemic Functional Grammar (SFG) by Halliday. The data of the study were 5 fictional narrative stories by third semester students of English Department, Faculty of Language and Arts, University of HKBP Nommensen Medan. The findings show that most of the stories are categorized into zig-zag non-linear pattern. This indicates that the students in developing their writings were not consistent and need guidance in writing narrative text.